The Saccharomyces cerevisiae 60 S Ribosome Biogenesis Factor Tif6p Is Regulated by Hrr25p-mediated Phosphorylation - Ray, Partha (American Society for Biochemistry and Molecular Biology, 2008)
The biosynthesis of 60 S ribosomal subunits in Saccharomyces cerevisiae requires Tif6p, the yeast homologue of mammalian eIF6. This protein is necessary for the formation of 60 S ribosomal subunits because it is essential for the processing of 35 S pre-rRNA to the mature 25 S and 5.8 S rRNAs. In the present work, using molecular genetic and biochemical analyses, we show that Hrr25p, an isoform of yeast casein kinase I, phosphorylates Tif6p both in vitro and in vivo. Tryptic phosphopeptide mapping of in vitro phosphorylated Tif6p by Hrr25p and (32)P-labeled Tif6p isolated from yeast cells followed by mass spectrometric analysis revealed that phosphorylation occurred on a single tryptic peptide at Ser-174. Sucrose gradient fractionation and coimmunoprecipitation experiments demonstrate that a small but significant fraction of Hrr25p is bound to 66 S preribosomal particles that also contain bound Tif6p. Depletion of Hrr25p from a conditional yeast mutant that fails to phosphorylate Tif6p was unable to process pre-rRNAs efficiently, resulting in significant reduction in the formation of 25 S rRNA. These results along with our previous observations that phosphorylatable Ser-174 is required for yeast cell growth and viability, suggest that Hrr25p-mediated phosphorylation of Tif6p plays a critical role in the biogenesis of 60 S ribosomal subunits in yeast cells.